A flexible, integrated film battery configuration for ultrafast sodium ion storage. Issue 2 (23rd December 2020) - Zhao, Wenyu; Wang, Helin; Li, Shaowen; Tang, Xiaoyu; Zhang, Min; Mustehsin, Ali; Bai, Miao; Liu, Siyuan; Sun, Changchun; Ma, Yue
Abstract : A flexible thin-film full cell prototype was fabricated by integrating a composite anode (1T-MoS2 /NCF) and a NASICON-type cathode (NVPF) onto both sides of a nano-AlO x modified polyethylene (AlO x -MPE) separator via the spin-coating process. Abstract : Flexible sodium-ion battery (SIB) design is hampered by the incompatible component integration at the device level, especially in consideration of the sluggish Na + diffusion kinetics, complex assembly technology and the electrode pulverization upon mechanical loadings. Herein, we develop a scalable spin-coating approach, through casting the cathode and anode slurries onto the both sides of an AlO x modified polyethylene (AlO x -MPE) separator, to construct a layer-stacked thin film battery configuration. The composite anode involves hierarchical structure design by vertically anchoring metallic phase (1T) MoS2 nanosheets on an interconnected nitrogen-doped carbon framework (namely 1T-MoS2 /NCF). For the cathode part, NASICON-type NaVPO4 F was directly integrated with the AlO x -MPE separator as the current-collector-free electrode. Upon the precise tuning of the areal capacity ratio of negative to positive electrodes (N/P ratio), the film battery prototype delivers a robust cyclability in the different deformation states as well as a maximized power output of ∼1049 W kg −1 . This integrated, thin-film battery configuration demonstrates tremendous potential in future flexible electronics.